ANALISIS WORTARTEN PADA KUTIPAN CERPEN ES IST KEIN GOTT AUßER ALLAH, UND MOHAMMED IST SEIN PROPHET BERBASIS WEBSITE UDPIPE UNTUK PEMBELAJARAN KOSAKATA BAHASA JERMAN - Irma Liani; Cahaya Mustika; Chairunnisa Nasution; Greace Simaremare (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to identify and describe Wortarten (word classes) in selected excerpts from the German short story Es ist kein Gott außer Allah, und Mohammed ist sein Prophet by utilizing the UDPipe website as a linguistic analysis tool. This research employed a qualitative descriptive method. The research data consisted of excerpts selected purposively because they were considered representative of various word classes in the German language. Data analysis was conducted using the tokenization, lemmatization, and part-of-speech tagging features available on the UDPipe website. The results revealed that the selected excerpts contain various types of Wortarten, including nouns (Nomen), verbs (Verben), adjectives (Adjektive), articles (Artikel), pronouns (Pronomen), prepositions (Präpositionen), conjunctions (Konjunktionen), adverbs (Adverbien), numerals (Numeralien), and interjections (Interjektionen). The most dominant word classes identified were verbs and adverbs, which play an important role in constructing meaning and narrative flow within the text. In addition to facilitating the systematic identification of word classes, the use of UDPipe also provides a practical means of understanding the grammatical functions of vocabulary items within sentence contexts. Therefore, the findings indicate that UDPipe-based Wortarten analysis can serve as an alternative approach to German vocabulary learning that is more contextual, systematic, and technology-enhanced.